Travel medicine training and experience among primary care physicians in Qatar - Ayman Al-Dahshan; Vahe Kehyayan; Noora Al-Kubaisi; Ziyad Mahfoud; Nagah Selim (PLoS ONE, 2025)
Background Travel medicine (TM) focuses on preventing and managing travel-related issues. Evidence has become more important than expert opinions in the development of TM standards. This study aimed to evaluate the training and experience of TM among Primary Care Physicians (PCPs) in Qatar and their associated factors. Methods A cross-sectional study design was employed. A structured questionnaire was utilized to gather data from all PCPs working in publicly funded primary health centers. Results The study involved 360 PCPs (response rate: 89.5%). Of these, 42.3% reported postgraduate training (15.1%) or experience (27.5%) in TM, with common training forms including workshops (67%), postgraduate programs (24%), and short courses (15%). About 81.8% expressed interest in TM training. Regarding confidence in practicing TM, 20% felt very confident, while 50% felt moderately confident. In practice, 25.8% conducted comprehensive pre-travel risk assessments, and 22.5% responded to traveler queries without formal consultations. Multivariable logistic regression analysis showed that PCPs who graduated from medical schools in Arab countries, conducting more than ten TM consultations per month, performing comprehensive pre-travel assessments, and those expressing high confidence were more likely to be associated with TM training or experience. Conclusion Many PCPs in Qatar lack prior training and experience in TM, raising concerns about their ability to provide adequate care to traveling patients. There is a significant need for targeted TM training for PCPs, especially since the majority express a keen interest in receiving such training.